2014
DOI: 10.1371/journal.pntd.0003128
|View full text |Cite
|
Sign up to set email alerts
|

Does Mass Azithromycin Distribution Impact Child Growth and Nutrition in Niger? A Cluster-Randomized Trial

Abstract: BackgroundAntibiotic use on animals demonstrates improved growth regardless of whether or not there is clinical evidence of infectious disease. Antibiotics used for trachoma control may play an unintended benefit of improving child growth.MethodologyIn this sub-study of a larger randomized controlled trial, we assess anthropometry of pre-school children in a community-randomized trial of mass oral azithromycin distributions for trachoma in Niger. We measured height, weight, and mid-upper arm circumference (MUA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…31,32 The effect of mass azithromycin distribution on nutritional status is less clear. 33,34 In this study population, another secondary analysis indicated that biannual distribution of azithromycin was associated with reduced under-5 mortality compared with annual distribution. 35 Overall, the distribution of oral azithromycin to this population may have affected the prevalence of both nutritional status and malaria in this setting.…”
Section: Discussionmentioning
confidence: 74%
“…31,32 The effect of mass azithromycin distribution on nutritional status is less clear. 33,34 In this study population, another secondary analysis indicated that biannual distribution of azithromycin was associated with reduced under-5 mortality compared with annual distribution. 35 Overall, the distribution of oral azithromycin to this population may have affected the prevalence of both nutritional status and malaria in this setting.…”
Section: Discussionmentioning
confidence: 74%
“…There is evidence from mass treatment trials for trachoma that macrolide administration reduced all-cause mortality, although it is unclear whether undernutrition mediated this effect [ 42 ]. Estimates from similar trials that compared the frequency of azithromycin administration for trachoma control have suggested some effect of more frequent azithromycin administration on linear growth [ 43 ]. Any observed benefit would have to be weighed against the potential harms of early antibiotic use, in particular selection for drug resistance and collateral effects on the gut microbiota [ 44–46 ].…”
Section: Discussionmentioning
confidence: 99%
“… 17 However, an effect on anthropometric outcomes has not been consistently shown in studies of mass azithromycin distribution for trachoma control. 18 , 19 Azithromycin has some activity against malaria and has been shown in some studies of mass distribution for trachoma to affect parasitemia and splenomegaly. 10 , 12 , 20 In the same study in which communities were measured at the same time points, azithromycin was effective at reducing the burden of malaria parasitemia.…”
Section: Discussionmentioning
confidence: 99%